Analisis Customer Perceived Value di Whiz Prime Hotel Khatib Sulaiman Kota Padang - Givo Sonesst; Rian Surenda (Departemen Pariwisata Universitas Negeri Padang, 2022)
The purpose of this study is to describe customer perceived value at Whiz Prime Hotel Padang. This research is motivated by several reviews about customer perceived value by guests who have stayed at Whiz Prime Hotel Padang. This research is quantitative descriptive research with survey method. The population of the study is guests who have stayed at the Whiz Prime Hotel in Padang city at least once, the number of samples is 100 people. Collecting research data using a questionnaire with a Likert scale that has been through validity and reliability tests. Data analysis uses descriptive analysis to see the categories of answers. The results of the study: overall showed a fairly good category with a percentage of 38% and obtained a TCR value of 65.10% a fairly good category. Furthermore, based on the following indicators: (1) The benefits of the product show a very good category with a percentage of 29% and obtain a TCR value of 66.5% with a fairly good category. (2) The service benefits show a fairly good category with a percentage of 31% and a TCR value of 66.75% with a fairly good category. (3) Personal benefits show a good enough category with a percentage of 35% and get a TCR value of 66.7% with a fairly good category. (4) The reputation benefit shows a fairly good category with a percentage of 28% and a TCR value of 64.25% in a fairly good category. (5) The cost of the price shows a fairly good category with an interpretation of the percentage of respondents' assessment of 39% and obtaining a TCR value of 63.8% with fairly good category. (6) The cost of labor and time shows a good category with the interpretation of the percentage of respondents' assessment of 26% and obtaining a TCR value of 63.08% with a fairly good category